Women who smoke and stop during pregnancy: who are they? Quem são as mulheres tabagistas que param de fumar na gestação? - Liane G. Reis; Cláudio Jerônimo da Silva; Arlene Trindade; Margarida Abrahão; Vilma Aparecida da Silva (Instituto Materno Infantil de Pernambuco, 2008)
OBJECTIVES: to identify factors involved in not stopping smoking in spite of being pregnant. METHODS: standardized interviews were applied to 486 pregnant women in the pre-natal clinics of four health centers in the city of Rio de Janeiro, Brazil, between April 2003 and February 2004. Every time a smoker was identified, an additional interview, which included the Edinburgh Postnatal Depression Scale, the Fagerströn scale for nicotine dependence, and the Screening Questionnaire for Adult Mental Disorders, was carried out. RESULTS: the prevalence of smoking, in the initial stages of pregnancy was 21.1%. Most smokers presented a low level of nicotine dependence. Thirty-six percent of them stopped smoking by the first trimester of the present pregnancy without any specific medical intervention. Important differences between those who were able to stop and those who were not were alcohol intake and number of previous attempts at abstinence. Women who stopped smoking drank less during gestation. CONCLUSIONS: stopping smoking during pregnancy seems to be linked to a non-specific drive towards the well-being of the fetus. The number of previous attempts at abstinence was positively related to stopping at the beginning of pregnancy. In spite of the prevalence of the problem, there is still inadequate support for smokers in the prenatal services. OBJETIVOS: identificar fatores envolvidos no comportamento de continuar fumando a despeito de estar grávida. MÉTODO: entrevistas padronizadas foram aplicadas a 486 mulheres grávidas nas clínicas de pré-natal de quatro centros de saúde na cidade do Rio de Janeiro, Brasil, no período de abril 2003 a fevereiro 2004. Todas as vezes que uma fumante era identificada, uma entrevista adicional foi aplicada, contendo a Escala de Edinburgh para Depressão, a escala de Fagerstron para dependência de nicotina e o Questionário de Avaliação de Doenças Mentais em adultos. RESULTADOS: a prevalência de tabagismo nos estágios iniciais da gravidez foi de 21,1%. A maioria das tabagistas apresentou baixo nível de dependência de nicotina. Trinta e seis por cento das mulheres avaliadas pararam de fumar no primeiro trimestre da gestação sem qualquer intervenção médica específica. As mesmas beberam menos durante a gestação e haviam tentado parar de fumar mais vezes anteriormente. CONCLUSÕES: os resultados sugerem uma motivação inespecífica para o bem estar do concepto que envolve as duas drogas lícitas. Aquelas que pararam, tentaram mais vezes anteriormente e também diminuíram o consumo de álcool na gestação atual.